Spatial-Temporal Accessibility and Inequality of Veterinary Service in Hong Kong: A Geographic Information System-Based Study - Ng, Ka Yiu; Ho, Chun Long; Koh, Keumseok (Frontiers in Veterinary Science, 2022)
Veterinary services are vital to the welfare of pets and their owners. Previous studies examined multiple factors affecting pet owners’ decision to consult vets, yet few studied the spatial accessibility of veterinary services. This study is one of the pioneering studies on the spatial-temporal accessibility of veterinary service and how it is associated with social and spatial inequality in Hong Kong. We measured the availability and accessibility of both general and 24/7 vet clinics using geographic information system. Then we found that the average district-to-district distances and the area of a district may explain the distribution pattern of general and 24/7 vet clinics by applying principal component analysis. In addition, social and spatial inequality of access to veterinary services was also observed as the accessibility of general vet clinics within walking distance is negatively correlated with household size and the number of public-housing and subsidized-housing households but positively correlated with the number of private-housing households. It suggests that the households living in private housing have higher accessibility to general veterinary services. The accessibility of 24/7 veterinary service is also positively correlated with the number of private housing households, households with the highest monthly household income, and population with a post-secondary degree, further shedding light on the social and spatial inequality issue that community with wealthier households and highly-educated population are more accessible to 24/7 veterinary services within walking distance.